If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 1) = 2(5 + -3x) Reorder the terms: 4(1 + x) = 2(5 + -3x) (1 * 4 + x * 4) = 2(5 + -3x) (4 + 4x) = 2(5 + -3x) 4 + 4x = (5 * 2 + -3x * 2) 4 + 4x = (10 + -6x) Solving 4 + 4x = 10 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 4 + 4x + 6x = 10 + -6x + 6x Combine like terms: 4x + 6x = 10x 4 + 10x = 10 + -6x + 6x Combine like terms: -6x + 6x = 0 4 + 10x = 10 + 0 4 + 10x = 10 Add '-4' to each side of the equation. 4 + -4 + 10x = 10 + -4 Combine like terms: 4 + -4 = 0 0 + 10x = 10 + -4 10x = 10 + -4 Combine like terms: 10 + -4 = 6 10x = 6 Divide each side by '10'. x = 0.6 Simplifying x = 0.6
| 6+3a= | | 7u-36=3(u-8) | | t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= |